Strategi Pengembangan Kawasan Wisata Sejarah Monumen Kresek Terintegrasi Agrowisata Berbasis Community-Based Tourism (CBT) di Kabupaten Madiun - Soebijantoro, Soebijantoro; Hartono, Yudi; Huda, Khoirul (Universitas Hamzanwadi, 2024)
This research aims to reveal the development of the Kresek Monument historical tourism area for agrotourism based on Community Based Tourism. Qualitative descriptive research method. Data collection through observation, interviews, focus group discussions, and document study. Data validity through source triangulation. Analyze data with interactive analysis. The results of the research show that the Kresek Monument historical tourist area needs to be developed with a new perspective that the landscape of the Kresek Monument historical tourist area has the potential to become a beautiful natural tourist destination. For a long time, the community has been actively involved in developing the Kresek Monument historical tourist area through the